Tháng Ba 1, 2024

Tính: \(A = \sqrt {{{\left( {\sqrt 5 – 1} \right)}^2}} + 1.\) \(B = \left( {2\sqrt 3 + \sqrt {20} } \right)\sqrt 3 – \sqrt {60} .\) A \(A = – \sqrt 5 \,;\,\,\,\,B = 4.\) B \(A = \sqrt 5 \,;\,\,\,\,B = 6.\) C \(A = 2\,;\,\,\,\,B = 5.\) D \(A = – 2\,;\,\,\,\,B = 4.\)

Tính: \(A = \sqrt {{{\left( {\sqrt 5 – 1} \right)}^2}} + 1.\) \(B = \left( {2\sqrt 3 + \sqrt {20} } \right)\sqrt 3 – \sqrt {60} .\)

A \(A = – \sqrt 5 \,;\,\,\,\,B = 4.\)

B \(A = \sqrt 5 \,;\,\,\,\,B = 6.\)

C \(A = 2\,;\,\,\,\,B = 5.\)

D \(A = – 2\,;\,\,\,\,B = 4.\)

Hướng dẫn Chọn đáp án là: B

Phương pháp giải:

Sử dụng công thức: \(\sqrt {{A^2}} = \left| A \right| = \left\{ \begin{array}{l}A\,\,khi\,\,A \ge 0\\ – A\,\,khi\,\,A < 0\end{array} \right.\)

Lời giải chi tiết:

\(A = \sqrt {{{\left( {\sqrt 5 – 1} \right)}^2}} + 1 = \left| {\sqrt 5 – 1} \right| + 1 = \sqrt 5 – 1 + 1 = \sqrt 5 \,\,\,\,\left( {do\,\,\,\sqrt 5 – 1 > 0} \right).\)

\(B = \left( {2\sqrt 3 + \sqrt {20} } \right)\sqrt 3 – \sqrt {60} = 2.3 + \sqrt {20.3} – \sqrt {60} = 6 + \sqrt {60} – \sqrt {60} = 6\)

Vậy \(A = \sqrt 5 \,;\,\,\,\,B = 6.\)

Chọn B.